Mitogen Activated Protein Kinases Functions in Signal Transduction and Human Diseases - Tikkanen, Ritva; Nikolic-Paterson, David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mitogen-activated protein kinases (MAPK) are a large family of enzymes that function as signal transducers to regulate a diverse range of physiological responses. However, signaling via extracellular signal-regulated kinase (ERK), c-Jun amino terminal kinase (JNK), and p38 MAPK also underpin many disease processes. This Special Issue provides new insights into how MAPK signaling contributes to specific pathological processes across a range of conditions, including disorders of lung development, type 2 diabetes, proliferative skin diseases, cardiovascular diseases, and neurological diseases.